Linguistic Occurrences in the Poetic Works of Lasgush Pogradeci PeculiaritÃ del linguaggio poetico di Lasgush Poradeci - Seitllari, Liri (Richtmann Publishing, 2012)
Article aims to discover the Lasgush Pogradeci's approach to the Albanian language ; to enlighten his opinion about thelanguage and its particular role in poetry.Therefor , we will stop at poetry